The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1590/s0100-55022006000100004
|View full text |Cite
|
Sign up to set email alerts
|

O ensino das relações trabalho-saúde-doença na escola médica: percepção dos alunos e proposta de aperfeiçoamento na UFMG

Abstract: RESUMODos médicos, independentemente da especialidade que exercem, são requeridas competências para lidar com as relações trabalho-saúde-doença, o que não tem sido adequadamente contemplado no curso de graduação. Buscando aperfeiçoar o ensino desse conteúdo, encontra-se em desenvolvimento, desde 2003, na Faculdade de Medicina da UFMG, com o apoio de duas bolsistas do Programa de Iniciação à Docência da Pró-Reitoria de Graduação, uma proposta de avaliar o programa da disciplina Saúde do Trabalhador, com ênfase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
4
0
4
Order By: Relevance
“…They also pointed to the awakening of the student as a health worker during the discipline, before taking the class, only 66.36% saw themselves as workers and after its end, 79.72% of students have considered themselves as workers. (4) In the UK, it was found the perception of physicians, nurses and health managers of the PHC about the conduction of occupational health actions, which identified deficiencies in training and the lack of training of these professionals, who reported they were not prepared to deal with issues relating to occupational health, the results of this study demonstrated the need to invest in continuing education in this area. (18) From this study we observed that the worker's health actions are part of the needs arising from professional practice in primary care and that PHC professionals need training that encompass the reality of population.…”
Section: ] (N8))mentioning
confidence: 77%
See 3 more Smart Citations
“…They also pointed to the awakening of the student as a health worker during the discipline, before taking the class, only 66.36% saw themselves as workers and after its end, 79.72% of students have considered themselves as workers. (4) In the UK, it was found the perception of physicians, nurses and health managers of the PHC about the conduction of occupational health actions, which identified deficiencies in training and the lack of training of these professionals, who reported they were not prepared to deal with issues relating to occupational health, the results of this study demonstrated the need to invest in continuing education in this area. (18) From this study we observed that the worker's health actions are part of the needs arising from professional practice in primary care and that PHC professionals need training that encompass the reality of population.…”
Section: ] (N8))mentioning
confidence: 77%
“…The undergraduate medical course should provide minimum competencies for professional understand the relationship between work and health of workers. (4) In another study assessing the design of nursing students on workers' health, the students stressed the importance of health education, accident prevention, direct assistance, the formation of support groups as predominant nursing activities. (14) The distance of health professionals about health and work issues are often one of the factors hindering the development of WH action.…”
Section: ] (N5))mentioning
confidence: 99%
See 2 more Smart Citations
“…Es necesario el desarrollo de modelos de promoción de la salud para los trabajadores subcontratados en el entorno estudiado. Estudos realizados na área de educação médica demonstram que a relação entre o trabalho e o processo saúde-doença não tem sido contempladas de forma adequada na formação dos estudantes 24 . Este cenário não é exclusivo do Brasil 25 e cerca de um terço das escolas médicas dos Estados Unidos não desenvolvem o tema de saúde ocupacional no programa dos cursos de graduação 26 .…”
unclassified